1997
DOI: 10.1046/j.1365-2168.1997.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of giant haemangioma of the liver

Abstract: Liver resection is the treatment of choice for giant haemangioma of the liver where possible. In selected cases liver transplantation is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
2
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 20 publications
0
72
2
5
Order By: Relevance
“…4,9 Surgical resection is the treatment of choice for a giant symptomatic hemangioma, and if it is unresectable, then liver transplantation may be considered. 10 Our experience indicates that resection of giant hemangioma of the liver is safe. The indication for resection, however, should be carefully analyzed before embarking on such a major operation.…”
Section: Discussionmentioning
confidence: 99%
“…4,9 Surgical resection is the treatment of choice for a giant symptomatic hemangioma, and if it is unresectable, then liver transplantation may be considered. 10 Our experience indicates that resection of giant hemangioma of the liver is safe. The indication for resection, however, should be carefully analyzed before embarking on such a major operation.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery includes liver resection, enucleation and transplantation [29]. A rare cases of liver transplantation performed for diffuse hepatic hemangiomatosis, lesions anatomically unresectable by conventional approaches and in patients with Kasabach-Merritt syndrome, have been reported [7][8][9][10]. However there is a shortage of liver graft and the need of a long-term anti-immunologic treatment in transplanted patients.…”
Section: Surgical Approachmentioning
confidence: 99%
“…A hemangioma can be removed by enucleation or liver resection however, most authors advocated enucleation procedure. In very rare and exceptional condition, Liver transplantation can be considered as a treatment option for hemangioma [7][8][9][10]. Other therapeutic options as Radiofrequency ablation (RFA) and transcatheter arterial embolization (TAE) can be considered in some situations.…”
Section: Introductionmentioning
confidence: 99%
“…Hemangiomas are the most common benign liver tumors and the second most common overall, with a prevalence of 0.4-7.3% found at autopsy, although other studies have suggested the prevalence of clinically relevant hemangiomas is 0.7-1.5% [1][2][3]. Liver hemangiomas can be characterized as normal or giant based on diameter, although there is no consensus regarding classification.…”
Section: Introductionmentioning
confidence: 99%